Development, democracy, and the state: critiquing the Kerala model of development - Ravi Raman, K. (Routledge contemporary South Asia series, 2010)
Caste, public action, and the Kerala model / KT Rammohan -- "Community" as de-imagining nation : relocating Narayana Guru and Ezhava movement in Kerala / J. Reghu -- Negotiating the Hindu state and nationalism : Travails in the making of a community / M.M.Khan -- Freedom, economic reform, and the Kerala "model" / M.A.Oommen -- On the periphery : Muslims and the Kerala model / M. Kabir -- Learning to learn : Dalit education in Kerala / Roshni Padmanabhan -- Revisiting the Kerala model : challening good health at low cost? / Caroline Wilson -- Asian Development Bank, conditionalities, and social democratic governance : Kerala model under pressure? / K Ravi Raman -- The conjuncture of "late socialism" in Kerala : a critique of the narrative of social democracy / Nissim Mannathukkaren -- Empowerment or politicization? : the limits of gender inclusiveness of Kerala's political decentralization / J. Devika and Binitha V. Thampi -- The institutionalization of dowry : feminine identity, conjugal patronage, and development / Praveena Kodoth -- "Caring" cosmopolitans and global migration : feminisation of migration / Shoba Arun -- Adivasi workers' struggles and the Kerala model of development : interpreting the past, confronting the present / Luisa Steur -- Social space, civil society, and transformative politics of new social movements in Kerala / T.T. Sreekumar
Includes bibliographical references and index
Keywords: 2000-2007; Kerala (India) -- Economic policy -- 21st century; Indien; Kerala; Konferenzschrift -- 2008 -- Manchester; Sozioökonomischer Wandel